2007
DOI: 10.1016/j.pain.2007.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis-induced vaginal hyperalgesia in the rat: Effect of estropause, ovariectomy, and estradiol replacement

Abstract: Endometriosis (ENDO) is a painful disorder defined by extrauteral endometrial growths. It is created in rats by autotransplanting pieces of uterus (which form cysts), or, for shamENDO, fat (no cysts). ENDO induces vaginal hyperalgesia, likely via central sensitization. The severity of this hyperalgesia correlates with estradiol levels during the estrous cycle, suggesting the hyperalgesia is estradiolmodulated. If so, then hyperalgesic severity should track estradiol changes during reproductive senescence (estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 28 publications
(44 reference statements)
2
65
0
Order By: Relevance
“…For example, when treated by combined OCs and progestogens, endometriotic lesions, pain symptoms, and nerve fiber density in ectopic and eutopic endometrium and myometrium are decreased and the levels of estrogen are reduced (8,17). It is suggested that the innervation of the endometrium and myometrium and pain symptoms in women with endometriosis are under the control of estrogen (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…For example, when treated by combined OCs and progestogens, endometriotic lesions, pain symptoms, and nerve fiber density in ectopic and eutopic endometrium and myometrium are decreased and the levels of estrogen are reduced (8,17). It is suggested that the innervation of the endometrium and myometrium and pain symptoms in women with endometriosis are under the control of estrogen (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…We chose, as an experimental model, 12 month-old female rats because only at 12 months is estrogen behavior similar to that occurring in human females at the onset of menopause (Berkley, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of estropause (12 months of age), female rats --like women --cycle irregularly, but after cycling ceases, 17-β estradiol levels in rats --unlike those in women and mice --fall not to zero, but to steady moderate levels (for two months) and then increase again (Berkley et al, 2007). So we can consider 12-month-old female rats to be in a similar condition to that occurring in women at the onset of menopause.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that, under the influence of estrogen, the endometrial stroma produces inhibitory signals for sympathetic nerves, whereas epithelial basal laminas retain their ability to support neuritic growth. The relatively recent finding of an abnormal presence of sympathetic and other nerves in eutopic endometrium and ectopic endometriotic growths in women with endometriosis (Tokushige et al 2006(Tokushige et al , 2007 and in ectopic cysts of rats with experimental endometriosis (Berkley et al 2004(Berkley et al , 2007 have increased the relevance of understanding in detail the mechanisms regulating the innervation of the endometrium and its responses to estrogen. Recent studies have demonstrated that increased levels of NGF and other trophic molecules contribute to the abnormal innervation observed in eutopic endometrium and ectopic endometriotic growths in women with endometriosis (Anaf et al 2002;Tokushige et al 2006).…”
Section: Substrate-bound Signals Contributes To Histotypic Patterningmentioning
confidence: 99%